2008
DOI: 10.1128/jb.00292-08
|View full text |Cite
|
Sign up to set email alerts
|

Rad50 Is Not Essential for the Mre11-Dependent Repair of DNA Double-Strand Breaks inHalobacteriumsp. Strain NRC-1

Abstract: The genome of the halophilic archaeon Halobacterium sp. strain NRC-1 encodes homologs of the eukaryotic Mre11 and Rad50 proteins, which are involved in the recognition and end processing of DNA double-strand breaks in the homologous recombination repair pathway. We have analyzed the phenotype of Halobacterium deletion mutants lacking mre11 and/or rad50 after exposure to UV-C radiation, an alkylating agent (N-methyl-N-nitro-N-nitrosoguanidine), and ␥ radiation, none of which resulted in a decrease in survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Similarly, rad50 and mre11 deletion mutant strains are viable in H. volcani and Halobacterium sp. NRC-1, as in E. coli and S. cerevisiae (Delmas et al, 2009;Kish and DiRuggiero, 2008). It is therefore intriguing that the radA, rad50, mre11, herA, and nurA genes seem to be essential in T. kodakaraensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, rad50 and mre11 deletion mutant strains are viable in H. volcani and Halobacterium sp. NRC-1, as in E. coli and S. cerevisiae (Delmas et al, 2009;Kish and DiRuggiero, 2008). It is therefore intriguing that the radA, rad50, mre11, herA, and nurA genes seem to be essential in T. kodakaraensis.…”
Section: Discussionmentioning
confidence: 99%
“…A few genetic investigations have been performed on the DNA repair genes, especially the HRR genes, in Haloferax volcani and Halobacterium sp. NRC-1, and showed that RadA functions in the repair of DNA damaged by ultraviolet (UV) irradiation and methyl methanesulfonate (MMS) (Woods and Dyall-Smith, 1997), and that Mre11 is important for the repair of DNA double-strand breaks in Halobacterium, whereas Rad50 is dispensable (Kish and DiRuggiero, 2008). The uvrA, uvrB and uvrC genes are required for the repair of UVinduced DNA photoproducts in Halobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
“…PFGE was performed as described previously (33), in triplicate. Following treatment, cells were pelleted by centrifugation at 8,000 ϫ g for 5 min and resuspended in room temperature BSS prior to being embedded into InCert agarose plugs (0.8% final concentration prepared in 3:1 BSS-H 2 O; Bio-Rad, Hercules, CA) at a final cell concentration of 1 ϫ 10 9 cells/ml.…”
Section: Mo) Escherichia Coli Andmentioning
confidence: 99%
“…The analyses of mre11 rad50 deletion mutants of the halophilic Halobacterium sp. strain NRC1 also suggest that Mre11 and Rad50 may have independent functions outside the MR complex in archaea, since the absence of Rad50 has no effect on the repair of DSBs, whereas the loss of Mre11 results in a decrease rate of DSBR, due to the loss of either nuclease activity or the DNA damage-sensing activity of Mre11 (Kish and DiRuggiero, 2008). Surprinsingly, the mre11 rad50 deletion mutant of Haloferax volcanii displays an enhanced resistance to DNA damage that correlates with a higher level of homologous recombination in the mutant, suggesting that Mre11-Rad50 restrains the use of HR for repair (Delmas et al, 2009).…”
Section: Physiological Roles Of Mre11-rad50 Complexmentioning
confidence: 99%